COMPARISON OF THE EFFECTIVENESS BETWEEN RED GALANGAL RHIZOME'S (Alpinia purpurata k.schum) EXTRACT AND KETOCONAZOL 2% TO INHIBIT GROWTH OF DERMATOPHYTE ​​FUNGI IN VITRO - Pangestuti, Dewi; Harris, Bilkes; Rahman, Tuti Khairani (Buletin Farmatera, 2020)
Red galangal rhizome (Alpinia purpurata k. Scum) has a larger size and has more therapeutic properties. Red galangal has compounds that can inhibit fungal growth namely flavonoids and saponins which can interfere with the function of the fungal cytoplasmic membrane, besides that they can cause leakage and aggregation of the outer cell membrane, which can inhibit the growth of dermatophytes. This study is a laboratory experimental study, using antifungal activity test with diffusion method using paper discs to see the comparison of the red galangal extract effectiveness and ketoconazole 2% on the growth of dermatophytes fungi Microsporum canis, Microsporum gypseum, and Trichophyton metagrophytes by measuring the inhibition zone around the fungal colonies. The concentrations of red galangal extract used were 10%, 20%, 30%, 40%, and 50% and used 2% ketoconazole as control. The data was analyzed using the One Way Anova test. Result of this study shown that all concentrations without 10 % of red galangal have inhibited zones of Microsporum canis, Microsporum gypseum, and Trichophyton metagrophytes but not better than ketoconazole 2 % activities.